(untitled) (Journal of Business, Universidad del Pacífico (Lima, Peru), 2023)
ASEAN countries have a limited impact on the trade of Pacific Alliance (PA) countries, although Chile and Peru have trade agreements with some of them. However, and parallel to an incipient growth in trade flows, there have been initiatives aimed at tightening links, both bilaterally and inter-regionally. The PA has stated its aim, in its Vision 2030, to promote external and inter-institutional relations, including deepening economic–trade cooperation with ASEAN. The objective of this study is to carry out an analysis of the trade and political ties between the Alliance members with the main ASEAN partners—Vietnam, Thailand, Indonesia, Malaysia, the Philippines and Singapore—taking into account the opportunities and challenges that arise. The research is descriptive based on a qualitative methodology that draws on the collection and interpretation of data, mainly secondar. In this regard, the documentary observation and document analysis techniques are used, among others.